2021
DOI: 10.3390/nu13072292
|View full text |Cite
|
Sign up to set email alerts
|

The Relevance of Obesity for Activities of Daily Living in Geriatric Rehabilitation Patients

Abstract: The obesity pandemic has reached old age but the effect of obesity on functional recovery in geriatric rehabilitation patients has not been investigated to date. In this prospective cohort study, patients admitted into geriatric rehabilitation were consecutively included between September 2015 and September 2016, aged ≥ 70 years. Individual activities of daily living were documented by the Barthel index (BI, 0-100 points). Obesity was assessed by the measurement of body mass index (BMI, kg/m²), waist circumfer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 22 publications
(24 reference statements)
3
4
0
Order By: Relevance
“…Despite the high prevalence of overweight and obesity found in this study, which is consistent with those found by other authors, some studies have associated elevated BMI in OA with lower mortality risk (Batsis et al, 2014;Chang et al, 2012). On the other hand, a high BMI in OA is also associated with dependence and cardiovascular problems (Gregson et al, 2019;Wojzischke et al, 2021). The fact that no underweight OA were found may reflect a favorable socioeconomic and cultural environment of the population studied (Chavarría et al, 2017;Osuna-Padilla et al, 2015).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Despite the high prevalence of overweight and obesity found in this study, which is consistent with those found by other authors, some studies have associated elevated BMI in OA with lower mortality risk (Batsis et al, 2014;Chang et al, 2012). On the other hand, a high BMI in OA is also associated with dependence and cardiovascular problems (Gregson et al, 2019;Wojzischke et al, 2021). The fact that no underweight OA were found may reflect a favorable socioeconomic and cultural environment of the population studied (Chavarría et al, 2017;Osuna-Padilla et al, 2015).…”
Section: Discussionsupporting
confidence: 92%
“…The prevalence of WC (≥ 88 cm) in women reported in this study, despite being high, was lower than that found by López-Ortega and Arroyo (2016) in Mexico and Gómez-Cabello et al (2011) in Spain (36.1% vs. 72.2% and 62.5% respectively), on the other hand, in men the prevalence of WC ≥ 102 was higher than in the two previous studies (65.7% vs. 33% and 34.1% respectively). Elevated WC has been associated with increased risk of frailty, dependency, cardiovascular disease and increased risk of mortality in OA (Gavriilidou et al, 2015;Hollander et al, 2012;Wojzischke et al, 2021;Xu et al, 2020), likewise, in post-menopausal women it has been associated with increased risk of hip fracture (Meyer et al, 2016) and in elderly women with type 2 diabetes mellitus it has been suggested that central adiposity may increase the risk of dementia (West et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the high prevalence of overweight and obesity found in this study, which is consistent with those found by other authors, some studies have associated elevated BMI in OA with lower mortality risk (Batsis et al, 2014;Chang et al, 2012). On the other hand, a high BMI in OA is also associated with dependence and cardiovascular problems (Gregson et al, 2019;Wojzischke et al, 2021). The fact that no underweight OA were found may reflect a favorable socioeconomic and cultural environment of the population studied (Chavarría et al, 2017;Osuna-Padilla et al, 2015).…”
Section: Discussionsupporting
confidence: 91%
“…Likewise, anthropometric measurements are associated with functional and health outcomes. For example, an increase in measures of adiposity has been associated with increased frailty, increased risk of falls, reduced functional performance, increased dependency, cardiometabolic risk and cardiovascular problems (Gregson et al, 2019;Khosravian et al, 2021;Kioh et al, 2019;Wojzischke et al, 2021;Xu et al, 2020;Zhang et al, 2021). On the other hand, a low body mass index (BMI) is also related to greater frailty and dependence (Xu et al, 2020;Zhang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%